The Effect of Products, Prices, and Advertising on the Purchase Decision of So Nice Sausage Products PT So Good Food (Japfa) in Sidoarjo: Pengaruh Produk, Harga, dan Iklan Terhadap Keputusan Pembelian Produk Sosis So Nice PT So Good Food (Japfa) di Sidoarjo - Luky Mardiyatno; Mudji Astuti (Academia Open, 2021)
This study aims to determine and analyze the effect of product, price and advertising on the Purchase Decision of So Nice Sausage Products PT So Good Food (Japfa) in Sidoarjo. This type of research is quantitative with causal nature. The object of this research is carried out by consumers who buy sausages so nice in the city of Sidoarjo by taking incidental sampling as many as 77 respondents. While the data instrument test uses validity and reliability tests, data collection techniques using questionnaires and data analysis techniques using multiple linear regression tests and hypothesis testing using t tests. The results of this study indicate that the Product variable influences the purchasing decision of So Nice Sausage Products PT So Good Food (Japfa), Price affects the purchasing decision of So Nice Sausage Products PT So Good Food (Japfa) and Advertising on the Purchase Decision of So Nice Sausage Products PT So Good Food (Japfa).